KECEMASAN MAHASISWA SELAMA STUDY FROM HOME (SFH) BERDASARKAN TEMPAT TINGGAL: STUDY ANXIETY LEVEL DURING STUDY FROM HOME (SFH) BY REGIONAL ORIGIN - Yuda Mustakim; Erni Astutik (Lembaga Penelitian dan Terapan untuk Kesehatan Jiwa (Lenterakaji), 2022)
ABSTRACT The Covid-19 pandemic has hit Indonesia since 2020, causing some activities to be limited, examples learning activities in universities. Therefore, many universities in big cities in East Java Implemented Study from Homesystem within (SFH) use’s video conferencing, messaging applications and campus platforms. The condition has impact for students’ psychological state during Study from Home (SFH) can be linked to. The purpose of the study was to determine whether there was a relationship between student anxiety and the increasing regional origin from students. This study used a cross-sectional analysis, data collection using a questionnaire distributed online through social media and broadcast messages, and the sample size used determined by sampling technique and calculated using the Lemeshow formula. The results that 56 respondents lived in urban areas with precentage 37.4% mild anxiety, 8.5% moderate anxiety, and experienced severe anxiety 6.9%. At the same time, the respondents who live in rural areas, as many as 50 respondents with precentage mild anxiety 33.6%, moderate anxiety 7.5%, and experienced severe anxiety 6.1%. In the interpretation of the data obtained, the p-value is 0.050, which means as a conclusion there is no significant relationship between residence and student anxiety levels during the SFH period. ABSTRAK Pandemi Covid-19 melanda Indonesia sejak tahun 2020 menyebabkan sejumlah aktivitas harus dibatasi seperti aktivitas pembelajaran di perguruan tinggi. Sehingga sejumlah perguruan tinggi di kota besar di Jawa Timur menerapkan sistem Study from Home (SFH) dengan penggunaan video conference, aplikasi pesan, serta platform kampus. Kondisi ini dapat dikaitkan dengan keadaan psikologis mahasiswa akibat adanya penerapan sistem SFH. Tujuan penelitian adalah untuk mengetahui hubungan antara kecemasan mahasiswa terhadap tempat tinggal , yaitu wilayah pedesaan dan perkotaan di Jawa Timur. Penelitian ini menggunakan pendekatan analsisis cross sectional pada mahasiswa yang berasal dari Jawa Timur. Metode Pengumpulan data menggunakan kuesioner di sebarkan melalui sosial media dan pesan broadcast. Besar sampel yang digunakan dalam penelitian ini di tentukan dengan teknik sampling dan dihitung dengan menggunakan rumus Lemeshow .Pada hasil penelitian terdapat 56 responden yang bertempat tinggal di daerah perkotaan dengan presentase kecemasan ringan 37.4%, kecemasan sedang s 8.5% dan kecemasan berat 6.9%. Sedangkan, sebanyak 50 responden bertempat tinggal di daerah pedesaan dengan presentase kecemasan ringan 33.6%, kecemasan sedang 7.5% dan kecemasan berat sebesar 6.1%. Hasil Interpretasi data yang diperoleh nilai p sebesar 0.050 yang berarti dapat di simpulkan bahwa tidak ada hubungan yang signifikan antara tempat tinggal dengan tingkat kecemasan mahasiswa selama masa SFH berlangsung.